Effect of tele nursing on the self-efficacy of patients with acute myocardial infarction (ST-segment elevation myocardial infarction, STEMI) in Cardiac Care Unit, Nakornping hospital, Chiang Mai province - Khanabkaew, Thamonwan; Tasiti, Wachiraporn; Jankaew, Kanokporn; Singsai, Pisanu; Kuntiya, Nirinrada; Khanabkaew, Cheeraya (Journal of Nakornping Hospital, 2025)
Introduction: ST-segment elevation myocardial infarction (STEMI) is a cardiac emergency that requires continuous rehabilitation after discharge, particularly enhancing self-efficacy. Objective: To study the effects of telenursing on self-efficacy among STEMI patients through telenursing via video calls. Study Method: This was a quasi-experimental study using a one-group pretest-posttest design conducted from August 25 to December 23, 2023. The study included STEMI patients diagnosed and admitted to the Cardiac Intensive Care Unit at Nakornping Hospital, aged 18 years and above, able to communicate in Thai, with access to the Speedy Tele system, not participating in other self-efficacy programs during the study, and without severe psychiatric history or communication impairment. Participants were purposively selected and received telenursing care via video calls once weekly for one month. Self-efficacy was assessed using the Cardiac Self-Efficacy Scale. Data were analyzed using descriptive statistics and the Wilcoxon signed-rank test. Results: A total of 36 patients participated. The majority were male (61.1%) with a mean age of 63±12.9 years. Common comorbidities included hypertension (44.4%) and diabetes mellitus (22.2%). The median cardiac self-efficacy score significantly increased from 2.53 (IQR 2.18–3.19) at baseline to 3.80 (IQR 3.61–4.00) post-intervention (p < 0.001). Before the telenursing intervention, the highest mean score was confidence in controlling chest pain through medication (3.08±0.77), while the lowest was confidence in maintaining sexual activity with spouse (1.63±1.30). After the intervention, the highest mean score was knowing when to call or visit a doctor (3.89±0.31), while confidence in maintaining sexual activity remained the lowest (2.75±1.16). However, this item had the fewest respondents (n=8). Conclusions: Telenursing effectively enhanced cardiac self-efficacy among STEMI patients. Telenursing interventions should be integrated as part of continuous care guidelines following hospital discharge.